(untitled) (Journal of the College of Basic Education, 2022)
The research dealt with one of the most important events witnessed by the Roman Empire at the beginning of its first imperial era until the middle of the first century AD, which is the turmoil of the internal situation during the reign of Emperor Nero and the revolutions and conspiracies that accompanied it, the result of which was that the emperor used the most horrific methods of torture and abuse of anyone who suspected or hated him. In addition to forcing prominent personalities to commit suicide and seize their property to compensate for the material losses that Nerurn spent, not satisfying his desires and whims, and thus this policy to the end of the rule of the family that Augustus founded to rule the Roman Empire